Strategy For Developing Micro, Small And Medium Enterprises Through Social Media: Case Study In Trisono Village - Diah Citra Fitriani; Ahmad Syafi'i SJ; Setia Dwi Ratna Rahmawati (JURNAL ECONOMINA, 2026)
his study aims to analyze the role of sosial media in the development of micro, small and medium enterprises in Trisono Village and to identify the challenges and strategies applied by business actors. The research uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The result show that sosial media plays an important role in expanding marketing, increasing consumer reach, and strethening interaction with customers. Instagram is the most widely used platform because it is effective for product promotion. Using sosial media also boosts the number of orders and sales revenue. The challenges faced include limited capital, low digital skills, and bussines competition. The strategies implemented optimizing promotion, improving product and service quality, product innovation, and developing digital skills.